1991
DOI: 10.1093/oxfordjournals.jbchem.a123586
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Basic Fibroblast Growth Factor at 1.6 Å Resolution

Abstract: We have determined the crystal structures of two types of human basic fibroblast growth factor, the serine analogue and the wild-type, at 1.6 and 2.5 A resolution, respectively. Two good heavy atom derivatives were found and used for multiple isomorphous replacement phasing. The atomic coordinates were refined using the Hendrickson & Konnert program for stereochemically restrained refinement against structure factors. The crystallographic R factors were reduced to 15.3% for the serine analogue structure and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 0 publications
2
56
0
1
Order By: Relevance
“…For FGF2, the crystal structure with the highest resolution (PDB code 1bgf) showed disorder for the ®rst 19±20 N-terminal residues (Ago et al, 1991), con®rmed by NMR studies of complete FGF2 (PDB code 1rml), which showed disorder for the N-terminal 28 residues (Moy et al, 1996). For FGF1 the crystal structure with the highest resolution (PDB code 2afg) showed disorder for the N-terminal 9±10 residues (Blaber et al, 1996); for the NMR structure (PDB code 1rml) a molecule N-terminally truncated at residue 25 was used (Lozano et al, 1998).…”
Section: Acta Cryst (2001) D57 378±384mentioning
confidence: 99%
“…For FGF2, the crystal structure with the highest resolution (PDB code 1bgf) showed disorder for the ®rst 19±20 N-terminal residues (Ago et al, 1991), con®rmed by NMR studies of complete FGF2 (PDB code 1rml), which showed disorder for the N-terminal 28 residues (Moy et al, 1996). For FGF1 the crystal structure with the highest resolution (PDB code 2afg) showed disorder for the N-terminal 9±10 residues (Blaber et al, 1996); for the NMR structure (PDB code 1rml) a molecule N-terminally truncated at residue 25 was used (Lozano et al, 1998).…”
Section: Acta Cryst (2001) D57 378±384mentioning
confidence: 99%
“…These assignments have led to the determination of the solution secondary structure for FGF-2, based on NOE data involving the NH, H α , and H β protons as well as 3 JH N H α coupling constants, amide exchange, and 13 C α and 13 C β secondary chemical shifts. Two crystal structures have been reported for FGF-2, where the protein is described as a β-sheet barrel of six antiparallel β-strands with a base of six additional β-strands (Zhu et al, 1983;Ago et al, 1991;Eriksson et al, 1991;Zhang et al, 1991). Comparison between the NMR secondary structure and the refined X-ray structure indicates clearly similar structures; however, some distinct differences exist, particularly at the heparin-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…This region forms a compact (3-barrel with 3-fold symmetry that is nearly identical in structure to the folded core of interleukins-la and -13 (18)(19)(20)(21). FGF-1 and FGF-2 also resemble interleukin-1,B in lacking a classical signal sequence.…”
mentioning
confidence: 99%